Psychological Changes and Employment Outcomes After Kyphosis Correction in Patients With Ankylosing Spondylitis. Issue 14 (15th July 2019) - Park, Jin-Sung; Kim, Young-Ho; Yang, Jae-Hyuk; Ko, Young-Il; Park, Ye-Soo
Abstract : Study Design: A retrospective study. Objective: To evaluate the psychological changes and employment outcomes following corrective osteotomy in patients with ankylosing spondylitis (AS). Summary of Background Data: To date, no study has investigated the changes in psychological status and subsequent improvement in employment outcome after correction of kyphotic deformities in patients with AS. Methods: This study included 48 patients with AS who underwent corrective osteotomy for severe kyphotic deformity. Sagittal alignment was assessed radiographically. Clinical status was evaluated using the Short Form-36 Health Survey, psychological status was evaluated using the Hospital Anxiety and Depression Scale (HADS), and employment outcomes were assessed using the Lam Employment Absence and Productivity Scale (LEAPS). The degree of postoperative sagittal alignment correction was measured, and changes in clinical and employment outcomes and psychological status were evaluated. The relationship between the degree of sagittal alignment correction and each evaluation item was analyzed. Results: Following postoperative sagittal alignment correction, all patients could stand erect and look straight. Significant improvements were observed in the clinical and employment outcomes, as well as in patients' psychological status. The degree of sagittal vertical axis correction was significantly correlated with the HADS depression and the LEAPS total scores. The degree of correction of the chin-brow vertical angle was significantly correlated with the Short Form-36 mental health score, the HADS depression and anxiety scores, and the LEAPS total and productivity subscores. Notably, the improvement in the HADS depression score was significantly correlated with the LEAPS total score. Conclusion: This study demonstrated the psychological changes and subsequent improvement in employment outcomes after corrective osteotomy in patients with AS. The degree of sagittal alignment correction was correlated with improvements in psychological status and employment outcomes. Level of Evidence: 4 Abstract : This study showed psychological changes and subsequent improvement in employment outcomes in patients undergoing corrective osteotomy for kyphosis. The degree of spinal sagittal alignment correction was significantly correlated with the improvements in psychological status and employment outcomes.